MAPPING OF SEAGRASS COVER ON CHLOROPHYLL-A, NITRATES AND PHOSPHATE IN THE TELUK AWUR, JEPARA - Sigit Febrianto; Nurul Latifah; Hadi Endarwati; Muhammad Zainuri; Suryanti Suryanti (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2019)
Teluk Awur Beach Jepara is one of the waters in Central Java that has a seagrass ecosystem. Seagrass role is the ability to support the life of another biota closely related to the fertility of the waters indicated by the content of chlorophyll-a, nitrate, and phosphate. The purpose of this study is to know the relationship between chlorophyll-a, nitrate, and phosphate to seagrass land cover as well as the variables which have major contributions. The method of study used is descriptive with four station sampling and  seagrass with a line transect of 50 m, and a 1x1 m² transect Quadrant divided into 16 sub plots measuring 25 x 25 cm² a spatial approach and multiple regression statistics. The results showed that there was a positive correlation between seagrass land cover to the concentration of chlorophyll-a and nitrate but less correlated phosphate. The highest chlorophyll-a concentrations of 0.381 mg/m3, seagrass land cover 40-60%, seagrass density 314 individual/m2, nitrate 1.141 mg/l and phosphate 0.54 mg/l. The lowest chlorophyll-a concentration ranges from 0.32-0.35 mg/m3, seagrass cover of 0-10%, seagrass density 3-12 individual/m2, nitrate 0.96 mg/l and phosphate 0, 21mg/L. This research shows that there is a strong link between seagrass land cover Concentrations of chlorophyll-a, nitrates and less influential to phosphates.